Assessment of the Suitability of Paper Waste as an Engineering Material - Okeyinka, O. M.; Idowu, O. J. (Engineering, Technology & Applied Science Research, 2014)
This research work investigates the potential applicability of waste paper in the production of ceiling boards with focus on achieving: environmental sustainability, safe disposal of waste paper and more cost effective production of materials. The main view was to provide an alternative to the conventional asbestos ceiling boards that are costly and also pose health risks. Three mix designs were formulated and used for the casting (1:1, 1:1.5 and 1:2), varying in regards of the weight of the waste paper components. CaCO3 was added to the mix as an additive as well as starch bond glue to aid binding. Laboratory experiments were conducted to determine the properties and suitability of the produced boards. Properties such as water absorption, abrasion, compressive strength, flexural strength and ultimate loads were considered for comparison. The boards with 1:1 mix ratio displayed the best results of the test properties hence, its mechanized manufacturing was recommended.